MGMAT official solution.
could someone please explain their explanation for the second statement? (in red below)
Bunuel"Before looking at the statements, make sure you understand what the question is asking. In particular, what is the connection between a, b, m, and n?
The function y = x^2 + ax + b is quadratic, so it can’t intersect the x-axis in more than two places. Since (m, 0) and (n, 0) are distinct x-intercepts, they must be the only two x-intercepts of the parabola. Therefore, the equation of the parabola can be written as y = (x – m)(x – n), which can be expanded into y = x^2 – mx – nx + mn, or y = x^2 + (–m – n)x + mn. Since this equation must be equal to the equation y = x^2 + ax + b, it follows that a = –m – n and b = mn.
(1) SUFFICIENT: We have equations that relate a and b to m and n. Replace a with (−m – n) and b with (mn):
4(mn) = (–m – n)2 – 4
4mn = m2 + 2mn + n2 – 4
4 = m2 – 2mn + n2
4 = (m – n)2
m – n = 2 or –2
Since the problem specifies that m < n, the first of these is impossible. Therefore, m – n = –2, or n – m = 2.
We can also deal with this statement by using smart numbers.
Solve the statement by dividing by 4, giving b = a^2/4 – 1. Then substitute values for a, solve for b, and then find m and n by solving the resulting quadratic.
· If a = 2, then b = 4/4 – 1 = 0. Therefore, the equation is y = x^2 + 2x, which factors to y = x(x + 2). The x-intercepts of this function are m = –2 and n = 0, so n – m = 2.
· If a = 4, then b = 16/4 – 1 = 3. Therefore, the equation is y = x^2 + 4x + 3, which factors to y = (x + 1)(x + 3). The x-intercepts of this function are m = –3 and n = –1, so n – m = 2.
· If a = 6, then b = 36/4 – 1 = 8. Therefore, the equation is y = x^2 + 6x + 8, which factors to y = (x + 2)(x + 4). The x-intercepts of this function are m = –4 and n = –2, so n – m = 2.
Try more cases if necessary (you may want to try a = 0, or a = negative); you’ll get n – m = 2 every time.
(2) INSUFFICIENT: If b = 0, then the equation is y = x2 + ax, where a is an unspecified constant. This equation factors to y = x(x + a) and so has x-intercepts –a and 0. Therefore, n – m = 0 – (–a) = a. Since a is unspecified, there are many possible values. We can also deal with this statement by using smart numbers.
We know b = 0; pick different values for a.
· If a = 1, then the equation is y = x^2 + x, which factors to y = x(x + 1). The x-intercepts of this equation are –1 and 0, so n – m = 0 – (–1) = 1.
· If a = 2, then the equation is y = x^2 + 2x, which factors to y = x(x + 2). The x-intercepts of this equation are –2 and 0, so n – m = 0 – (–2) = 2.
We have found two different values for n – m, so this statement is insufficient.
The correct answer is A.